Mind the Rural Investment Gap : Disparities in Access to Basic Infrastructure and Directions for Mozambique’s Public Investment Program - World Bank (World Bank, Washington, DC, 2020)
Against the backdrop of increasing income inequality, this report uses spatial analysis to assesses whether disparities in access to basic infrastructure between Mozambique's lagging and leading regions are growing or declining and whether the public expenditure program is effective in addressing emerging disparities. The report finds that overall, the gap has been growing between rural and urban areas, especially in the rural parts of Mozambique's central and northern provinces – which are the poorest. It also found that Mozambique's public investment program has made limited progress in reducing access disparities, including during the investment boom years. Lower investment levels in underserved areas, combined with spending inefficiencies, contributed to increased gaps in access. The report concludes with recommendations for better targeting of public investments to reach underserved areas.